Nature’s touch: engaging children’s sensory learning and development through nature-based play - Coulter, Michaela (My University, 2025)
Full of stimulating elements, nature provides a dynamic setting where children engage all of their senses and deepen their understanding of the world. Play is essential to a child’s physical, cognitive, and social development, and playing in nature simultaneously engages a child’s sensory learning and development. By incorporating natural elements into early childhood spaces, children become more attuned to themselves, others, and the environment around them. Designing outdoor play spaces that engage all of their senses in early childhood enhances their cognitive and physical development, social skills, emotional regulation, and creativity. The goal of this research design is to explore the landscape architect’s role in creating play environments that nurture sensory development in early childhood. The primary outcome from the research project will be a projective design for the Kansas State University Center for Child Development (CCD), focused on enhancing sensory experiences in a nature-based environment for young children. Serving the K-State and Manhattan communities, the CCD provides child care and a rich learning environment, prioritizing nature-based learning and exploration through its evidence-based practices. To inform this design, an in-depth literary review, analysis of existing nature-based play guidelines, and exploration of built works was conducted, providing design considerations for engaging sensory integration patterns and the seven main senses in a nature-based play environment. Beyond the CCD, this project sought to highlight the importance of sensory-rich play in early childhood and provide a framework to help landscape architects when designing similar settings.
Keywords: Playground design; Nature-based play; Sensory play; Sensory development; Nature play guidelines; Early childhood design